Animal models of chronic traumatic encephalopathy - Kelly M McAteer; Renee J Turner; Frances Corrigan (Concussion)
Repeated head impacts have been suggested to be associated with the development of the neurodegenerative disorder, chronic traumatic encephalopathy (CTE). CTE is characterized by the accumulation of hyperphosphorylated tau within the brain, with accompanying cognitive and behavioral deficits. How a history of repeated head impacts can lead to the later development of CTE is not yet known, and as such appropriate animal models are required. Over the last decade a number of rodent models of repeated mild traumatic brain injury have been developed that are broadly based on traditional traumatic brain injury models, in controlled cortical impact, fluid percussion and weight drop models, with adaptations to allow for better modeling of the mechanical forces associated with concussion.